Effect of sowing and weed control methods on nutrient uptake and soil fertility in direct-seeded rice (Oryza sativa) - PRATAP, VIJAY; VERMA, S K; DASS, ANCHAL; YADAV, DEEPAK KUMAR; MADANE, A J; MAURYA, RAKESH; JAYSAWAL, PEEYUSH KUMAR (The Indian Journal of Agricultural Sciences, 2021)
A 2-year field experiment consisting of 3-planting methods and 5-weed control options was conducted in a three-time replicated split-plot design at Varanasi during kharif 2016-17 to assess the nutrient uptake by direct-seeded rice (Oryza sativa L.) and available nutrient status of soil under different methods of establishing crop and managing weeds. Zero-till direct-seeded rice (ZT-DSR) + residue + Sesbania brown manuring (SBM) recorded lower density and dry-weight of weeds, higher organic carbon (OC), available N, P and K in soil and enhanced N, P and K uptake by 8.9, 6.7, 7.8% and 23.7, 24.5 and 10.2% in grain and straw, respectively, over conventionally-tilled direct-seeded rice (CT-DSR) + SBM. Among weed control options, the use of pendimethalin (1000 g/ha) fb chlorimuron + metsulfuron (4 + 4 g/ha, 25 DAS) + 1 HW (45 DAS) resulted in lower density and weeds, higher OC, available N, P and K in soil and improved N, P and K uptake in grain and straw by 23.6, 20.9 and 33.0 and 26.7, 25.5 and 26.6%, respectively over weedy check. However, higher EC and pH and lower nutrient (N, P and K) and protein content in grain and straw were found under weed-free condition. Overall, ZT-DSR + residue + SBM and application of pendimethalin (1000 g/ha) fb chlorimuron + metsulfuron (4 + 4 g/ha, 25 DAS) + 1 HW (45 DAS) proved better with respect to reduction in weed biomass, OC, available soil nutrients (N, P and K) and their uptake in DSR.